Spatial dispersion modeling of air emissions from a farm using a Gaussian model. Issue 4 (11th May 2021) - Fakinle, Bamidele Sunday; Odekanle, Ebenezer Leke; Okunlola, Oyinkansola Serah; Oke, Daniel Olawale; Aremu, Charity O.; Sonibare, Jacob Ademola; Akeredolu, Funso Alaba
Abstract: Agricultural activities may cause significant air pollution at the local, regional, and global scales due to the uncontrolled release of pollutants into the environment. This study therefore provided model‐based spatial estimates of ground‐level concentrations of air emissions from Landmark University Farm. The emission inventory and meteorological parameters of the farm were used to execute a Gaussian dispersion model over a distance of 2 km. Elevated ground‐level concentrations were recorded, which continued to decrease as the distances increased. These concentrations exceeded threshold limits stipulated by National Ambient Air Quality Standard. The study concluded that high levels of air emissions obtained in this study are indications of tendencies for possible violation of permissible limits at locations not too far from the University Farm.